A shared page-aware machine learning assisted method for predicting and improving multi-level cell NAND flash memory life expectancy. (January 2023) - Santikellur, Pranesh; Buddhanoy, Matchima; Sakib, Sadman; Ray, Biswajit; Chakraborty, Rajat Subhra
Abstract: NAND flash memory is widely used in consumer electronics, personal computers, and enterprise data storage servers. The most prevalent source of flash memory errors is retention errors, which are mainly caused by leakage of charges. It has been observed that inside the chip, some flash memory blocks exhibit greater endurance to the retention errors than others. In an effort to prolong life expectancy, previous studies focus on improving the Raw Bit Error Rate (RBER) metric at page and block levels, without due consideration of the geometry of shared pages. In this paper, the first insight we provide is that groups of shared pages have different RBER values, and should be analyzed separately. We use this insight to construct a machine learning model to predict the blocks which have less endurance, using the characterization data of new unused flash memory chip(s). This is accomplished by extracting location-sensitive and value-sensitive features from the shared pages group, and engineering them into more sophisticated and explainable features. Furthermore, we describe how our proposed prediction model can be used in combination with the existing flash translation layer (FTL) wear-leveling algorithm to increase lifetime. We evaluated the proposed prediction and lifetime improvement method for four different machine learning techniques, among which Support Vector Machine (SVM) achieved superior accuracy up to 85% at a lower computational overhead. Highlights: NAND Flash. Machine learning. Life Improvement. MLC Flash Reliability. Shared Pages.